INTEGRASI ANTARA AKIDAH DAN ILMU PENGETAHUAN DAN TEKNOLOGI: PERSKPEKTIF AL-QUR’AN - Sinaga, Ali Imran; Darlis, Ahmad; Nst, Ahmad Husein; Debataraja, Christina Suriani; Witjaksana, Mega (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
The progress and development of science and technology that humans sometimes achieve cannot be separated from human exploration of the universe and its contents. The reason is that science and technology seek sources of knowledge from nature. And Islam, the religion sent down by Allah, which calls on humans to explore and experiment with nature, was one of the factors in this progress. Through the integration of faith and science and technology, it is hoped that various weaknesses and setbacks of Muslims can be corrected, so that they can again feel the progress and glory achieved by Muslims in classical times. This will also affect Islamic education which is expected to survive the rapid development of science and technology in this century. This research uses the library method or library research. The collection of data from this research comes from reading sources related to this discussion. The results of the research is synthesis or a combination of religion and science is the unification of human understanding, both of which are a unity of truth. Both come from the Almighty, namely Allah SWT. Both work side by side to fill human life.